2021
DOI: 10.3389/fmars.2021.612016
|View full text |Cite
|
Sign up to set email alerts
|

A New Marine Biomaterial: The Shell of Mangrove Horseshoe Crabs, Carcinoscorpius rotundicauda (Latreille, 1802) Emphasizing Its Physico-Chemical Characteristics

Abstract: The paper aims to elucidate the physico-chemical characteristics of the shell of mangrove horseshoe crabs (Carcinoscorpius rotundicauda) and determine the compilation matrix for the first time. The shell composition matrix of C. rotundicauda has never been studied in detail before, especially the shape of the foam, the chemical composition, the functional groups and the mechanical-physical and thermal properties of the shell. Based on this study, the shell structure of the mangrove horseshoe crab has the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…The structure has a rough surface, forms a porous structure, and the pore distribution is less uniform. The hollow structure reinforced with struts is thought to function as a mobility component and shellfish defense [1].…”
Section: Characteristics Of the Structure Of The Prosoma Of Tachypleu...mentioning
confidence: 99%
See 2 more Smart Citations
“…The structure has a rough surface, forms a porous structure, and the pore distribution is less uniform. The hollow structure reinforced with struts is thought to function as a mobility component and shellfish defense [1].…”
Section: Characteristics Of the Structure Of The Prosoma Of Tachypleu...mentioning
confidence: 99%
“…This analysis showed that the acoustic impulse response could potentially be a non-destructive test for protected biota, and the structure of the horseshoe crab prosoma has the potential to be a bioinspired material. A biomimetic approach needs to be used to study the combination of constituent elements, such as polysaccharides and minerals, in the shell of C. rotundicauda as a guide for developing new materials with the same properties from synthetic materials without going overboard with one particular species [1]. Ha and Lu [18] said that the shape of the prosoma structure is included in the category of bioinspired structure for energy absorption or bioinspired honeycombs (corrugated honeycombs).…”
Section: Acoustic Waves Of the Structure Of Tachypleus Gigas And Carc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although they feature many stochastic cellular structures, these have received relatively little attention in terms of their mechanical properties of the parameters of the pores [13,14]. Due to the large size of their round prosoma, its structural stability and resistance especially in terms of the gradient distribution its cuticle thickness, lip thickening, and the filling of the cellular structure in specific regions, have been investigated [15,16]. Tissues with a cellular structure allow for a strong specific strength, bending stiffness, and superior energy absorption [17].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the mangrove horseshoe crab Carcinoscorpius rotundicauda has no commercial importance in India except for indigenous (Noida) preparation into health tonics and pain-relief ointment and the sparring collection for biomedical research (John et al, 2018). Elsewhere with similar opinions, the dried carapace of C. rotundicauda is used for bioactive compound research (Alam et al, 2015;Luo et al, 2020;Wardiatno et al, 2021;Xu et al, 2021). With horseshoe crab chitosan, specifically sourced from the dried carapace of C. rotundicauda claimed to have the lowest molecular weight than other marine sources, the present study explores on the use of heat radiation [via gamma (γ) irradiation] to further reduce the molecular weight of the derived chitosan for enhanced antimicrobial capability.…”
Section: Introductionmentioning
confidence: 99%